PENYUNTINGAN BAHASA DALAM PANDANGAN ISLAM - Husniah Ramadhani Pulungan (IAIN Padangsidimpuan, 2016)
One of a very vital human life needs is to communicate to others. But sometimes the communication makes misunderstandings due to the language spoken. Therefore, for long time ago had warned that to communicate people must use good speech. Good speech will come from the good soul and good thinking. If someone is able to speak in good speech, then it can be stated that someone has been redaction their own language. Because with the redaction their language, it will be very good in Islam, and also will be able to maintain relationships of muamalah. If this can be done continuously, it will create a strong brotherhood among Muslims.